Implementing Project-Based Learning to Enhance Students' Reading Skills in Report Text - Zubaedah Wiji Lestari; Kunkun Kurniady; Supian Supian; Erik Rusmana (Universitas Galuh, 2023)
This study concentrated on using project-based learning to help students become more proficient readers, particularly of report texts. This study had two goals, the first is to examine how project-based learning can be used to help students become better readers specially on report texts. Moreover, the study aims to track students' reactions to the implementation of project-based in reading learning. Mixed method design was used as the research design for this study. Additionally, the researchers used several instruments to gather data, including observation sheets, reading tests for students, questionnaires, and interview questions. The study's findings showed that project-based learning, when used to teach students in reading reports text with common themes and constant teacher guidance throughout the reading process may enhance students' reading comprehension. The average score of the students' reading tests taken chronologically shows that the students enhance their reading skills in the report text. The results also demonstrated that students responded positively to the implementation of project-based learning in reading report text. The opinions of the students demonstrated that they believed project-based learning improved their comprehension of the content of the report text. Additionally, since project-based learning enables students to read more comprehensively, it is advised that English teachers use it to teach reading skills for other genres of texts and other language skills.